Conformational Clamping by a Membrane Ligand Activates the EphA2 Receptor. Issue 18 (3rd September 2021) - Westerfield, Justin M.; Sahoo, Amita R.; Alves, Daiane S.; Grau, Brayan; Cameron, Alayna; Maxwell, Mikayla; Schuster, Jennifer A.; Souza, Paulo C.T.; Mingarro, Ismael; Buck, Matthias; Barrera, Francisco N.
Graphical abstract: Highlights: Inhibition of the EphA2 receptor drives cancer malignancy by promoting metastasis. The TYPE7 peptide binds to and activates the transmembrane domain of EphA2. TYPE7 stabilizes the active conformation by membrane scaffolding. Molecular clamping of the transmembrane domain might be a widespread mechanism of activation. Abstract: The EphA2 receptor is a promising drug target for cancer treatment, since EphA2 activation can inhibit metastasis and tumor progression. It has been recently described that the TYPE7 peptide activates EphA2 using a novel mechanism that involves binding to the single transmembrane domain of the receptor. TYPE7 is a conditional transmembrane (TM) ligand, which only inserts into membranes at neutral pH in the presence of the TM region of EphA2. However, how membrane interactions can activate EphA2 is not known. We systematically altered the sequence of TYPE7 to identify the binding motif used to activate EphA2. With the resulting six peptides, we performed biophysical and cell migration assays that identified a new potent peptide variant. We also performed a mutational screen that determined the helical interface that mediates dimerization of the TM domain of EphA2 in cells. These results, together with molecular dynamic simulations, allowed to elucidate the molecular mechanism that TYPE7 uses to activate EphA2, where the membrane peptide acts as a molecular clamp that wraps around the TM dimer of the receptor. We propose that this binding mode stabilizes the active conformation of EphA2. Our data, additionally, provide clues into the properties that TM ligands need to have in order to achieve activation of membrane receptors.